219k views
1 vote
Y÷2+x;use x =1, and y = 2

2 Answers

1 vote

y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2y ÷ 2 + x; use x = 1, and y = 2

User Shane N
by
5.7k points
2 votes
Y/2+x
2/2+1
1+1
2
Hope this helps
GENERAL OUT
User Bob Flannigon
by
6.7k points